EVALUASI KUALITAS TEKNIS SISTEM INFORMASI ADMINISTRASI COASS MENGGUNAKAN GOOGLE LIGHTHOUSE - Made Dhyo Pradnyadiva; Ngurah Indra ER; Fajar Purnama; Komang Sri Utami; I Wayan Shandyasa (Jurnal SPEKTRUM, 2025)
The successful adoption of an information system is highly dependent on its technical quality, including performance, accessibility, adherence to Best Practices, and SEO compliance. This study aims to evaluate the technical quality of a web-based information system for Coass (clinical internship) administration using Google Lighthouse. The audit was conducted on three key user interfaces: the Admin, Doctor, and Student Dashboards. The evaluation focused on four main categories: Performance, Accessibility, Best Practices, and SEO. The results demonstrated outstanding scores across all tested pages, with Performance scoring between 99–100, Accessibility at 95–96, and perfect scores (100) in both Best Practices and SEO. These results confirm that the system exhibits a high level of technical quality and aligns with modern web development standards. The findings indicate that the system delivers not only functional capabilities but also speed, reliability, and a highly optimized user experience.